1988
DOI: 10.1063/1.340775
|View full text |Cite
|
Sign up to set email alerts
|

Heavy fermion behavior in CePtSi and CeRuSi

Abstract: We present results of specific heat, electrical resistance, and magnetic susceptibility measurements on the heavy fermion system CePtSi and compare it to CeRuSi. Both compounds show a low-temperature maximum in cp/T, usually associated with the formation of a coherent heavy fermion ground state. An additional feature in cp/T is observed for CePtSi and is attributed to cooperative magnetism, an interpretation confirmed by magnetic measurements. A comparison with other heavy fermion systems, especially stoichiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
5
12
1
Order By: Relevance
“…The tetragonal compound CePtSi has been found to show both some kind of magnetic order near 3 K and a y below 1 K of 840 mJ/mol Ce K 2 [12]. Shelton et al [13] have also worked on this material• Sereni et al [14] have found the extremely large y = 3.9 m J/tool Ce K 2 in the cubic CePd3B.…”
Section: Unusual Materials 33 Other Structuresmentioning
confidence: 96%
“…The tetragonal compound CePtSi has been found to show both some kind of magnetic order near 3 K and a y below 1 K of 840 mJ/mol Ce K 2 [12]. Shelton et al [13] have also worked on this material• Sereni et al [14] have found the extremely large y = 3.9 m J/tool Ce K 2 in the cubic CePd3B.…”
Section: Unusual Materials 33 Other Structuresmentioning
confidence: 96%
“…In the present paper, we will discuss the effect of hydrogenation on the ternary silicide CeRuSi, which crystallizes in the tetragonal CeFeSi-type structure and is considered as a nonmagnetic heavy-fermion system. 13 Its investigation by specific heat ͑C p ͒ measurements reveals a shallow maximum at 0.5 K and an electronic coefficient ␥ = C p / T = 220 mJ/ mol K 2 , which is indicative of a moderate heavy-fermion character. This low-temperature behavior can be associated with the formation of a coherent heavyfermion ground state, and the analysis of the specific heat measurements within the one-impurity Kondo model has suggested a large Kondo temperature of the order of 25 K. 13 The absence of magnetic ordering for CeRuSi was confirmed above 4.2 K by neutron powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…13 Its investigation by specific heat ͑C p ͒ measurements reveals a shallow maximum at 0.5 K and an electronic coefficient ␥ = C p / T = 220 mJ/ mol K 2 , which is indicative of a moderate heavy-fermion character. This low-temperature behavior can be associated with the formation of a coherent heavyfermion ground state, and the analysis of the specific heat measurements within the one-impurity Kondo model has suggested a large Kondo temperature of the order of 25 K. 13 The absence of magnetic ordering for CeRuSi was confirmed above 4.2 K by neutron powder diffraction. 14 Finally, x-ray absorption spectroscopy at the Ce L III edge gives a measured valence of 3.14 for cerium in this ternary silicide.…”
Section: Introductionmentioning
confidence: 99%
“…The non-centrosymmetric crystal structure of the CePt 3 B-type is adopted also in the CePt 3 Si case, although the ratio between the B and Si atomic radii R is considerably large R B /R Si = 0.74. On the other hand, the atomic radii of Ru and Pt are very close (R Ru /R Pt = 0.96) and there are many examples of formation of isostructural Ru-and Pt-containing analogous compounds in literature [2,22,23]. However, it does not hold for CeT 3 Si with Pt and Ru [24].…”
Section: Samples S1-s5mentioning
confidence: 85%